2011
DOI: 10.1186/1743-0003-8-32
|View full text |Cite
|
Sign up to set email alerts
|

Automatic identification of gait events using an instrumented sock

Abstract: BackgroundTextile-based transducers are an emerging technology in which piezo-resistive properties of materials are used to measure an applied strain. By incorporating these sensors into a sock, this technology offers the potential to detect critical events during the stance phase of the gait cycle. This could prove useful in several applications, such as functional electrical stimulation (FES) systems to assist gait.MethodsWe investigated the output of a knitted resistive strain sensor during walking and soug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Unfortunately, although the authors described a dynamic walking test, no quantitative results were reported. On a related front, Preece et al [38] created an instrumented sock to identify heel strike, heel lift, and toe off during the gait cycle. The sock contained knitted strain sensors formed using the characteristics of the knitting pattern, which allowed loops of conductive yarn to come into or out of contact with each other as the fabric stretched, decreasing or increasing the effective length of the conductor and proportionally, the resistance.…”
Section: Textile Innovationsmentioning
confidence: 99%
“…Unfortunately, although the authors described a dynamic walking test, no quantitative results were reported. On a related front, Preece et al [38] created an instrumented sock to identify heel strike, heel lift, and toe off during the gait cycle. The sock contained knitted strain sensors formed using the characteristics of the knitting pattern, which allowed loops of conductive yarn to come into or out of contact with each other as the fabric stretched, decreasing or increasing the effective length of the conductor and proportionally, the resistance.…”
Section: Textile Innovationsmentioning
confidence: 99%
“…Some research papers describe textile implementations for actigraphy and gait analysis. These works show the development and implementation of smart socks with embedded pressure and strain sensors [6][7][8][9][10][11][12], and they have shown results in movement classification. However, embedding electronics in a sock usually take place outside the textile structure, which makes it uncomfortable to the user and could affect normal gait conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Aimed to reduce the intrusion while gathering data, e-textiles can track different kinds of phenomena (Fleury, Sugar, & Chau, 2015), such as strain (Gioberto & Dunne, 2013;Giorgino, Tormene, Lorussi, de Rossi, & Quaglini, 2009;Preece et al, 2011;Tormene et al, 2012;Yamada et al, 2011), acceleration (Harms, Amft, & Troester, 2010;Zysset et al, 2013), joint movements (Lee, Lee, Kim, & Lee, 2011), bend angle (Lorussi, Galatolo, & Bartalesi, 2013), posture (Di Rienzo et al, 2009), or pressure (Shu et al, 2010).…”
Section: Quantified-self Wearable Devicesmentioning
confidence: 98%